Calcium Distribution Patterns of the Aorta as Predictors of Significant Coronary Artery Disease in Patients with Moderate to Severe Aortic Stenosis - Thonghong, Tasalak; Deetes, Sivayos; Suwannasom, Pannipa; Kuanprasert, Srun (Biomedical Sciences and Clinical Medicine, 2025)
OBJECTIVE Computed tomography (CT) of the aortic valve and aorta has gained a greater role in planning for aortic valve replacement (AVR). However, when AVR is planned, invasive coronary angiography remains the standard investigation. Whether the calcium distribution pattern in the aorta predicts the significant presence of coronary artery disease (CAD) in patients undergoing AVR remains unclear. This study evaluated the correlation between the calcium distribution pattern from the CT aorta to predict significant CAD in patients with symptomatic moderate to severe aortic stenosis undergoing AVR. METHODS This retrospective study included candidates for AVR either with transcatheter replacement (TAVR) or surgical replacement (SAVR) at a single tertiary-care center between 2017 and 2022. The calcium distribution patterns from the left ventricular outflow tract up to the descending aorta were analyzed from the non-contrast CT of the aorta. Significant CAD was identified from invasive coronary angiography and was defined as 50% diameter stenosis (DS) of the left main and 70% DS of the proximal left anterior descending artery. Multivariate logistic regression analysis was performed to identify the calcification pattern associated with the significant CAD. RESULTS In total, 110 patients were included in the analysis. Among them, 40 patients (36.4%) were candidates for TAVR, while 70 patients (63.6%) were candidates for SAVR. The prevalence of significant CAD was 12.7%. Baseline characteristics were similar between patients with and without CAD, with the exception of a higher prevalence of chronic kidney disease in the CAD group (42.9% vs. 19.8%, p = 0.01). The presence of calcium at the ostium of the coronary artery and descending aorta was an independent predictor of significant CAD (OR 3.44, 95% CI1.30-9.10, p = 0.01 and OR 12.03, 95% CI 1.14-126.84, p = 0.04). CONCLUSIONS This pilot study showed that calcium at the ostium of the coronary artery and descending aorta from non-contrast CT aorta was associated with significant CAD in patients with moderate to severe AS. Further study with more subjects be needed to confirm the findings.